Lexington : the extraordinary life and turbulent times of America's legendary racehorse - Wickens, Kim (Ballantine Books, 2023)
"The dramatic true story of the champion Thoroughbred racehorse who gained international fame in the tumultuous, Civil War-era South, despite going nearly blind, and became the most successful sire in American racing history. The early days of American horse-racing were grueling. Four-mile heats-races four miles long, run two or three times in succession!-were the norm, rewarding horses who possessed the ideal combination of stamina and speed, attributes that pioneering Americans prized. The stallion Lexington, named after the city in Kentucky where he was born, exemplified these winning qualities, encouraging a war-torn nation in those perilous times that the extraordinary was possible. After shattering the world speed record for a four-mile race, Lexington continued his winning career until deteriorating eyesight forced his retirement in 1855. But once his groundbreaking achievements as a racehorse ended, his role as a sire began. Horses from his bloodline won more money than the offspring of any other Thoroughbred sire-an annual success that led Lexington to be named America's leading sire an unprecedented sixteen times. Yet with the Civil War raging, Lexington's years at a Kentucky stud farm were far from idyllic. Confederate soldiers ran amok, looting freely and kidnapping horses from the top stables. They soon focused their desires on the prized Lexington and his valuable progeny. Kim Wickens, a lawyer and dressage rider, became fascinated by this legendary horse when she learned that twelve of Thoroughbred racing's thirteen Triple Crown winners descend from Lexington. She spent years meticulously researching the horse and his legacy-and with Lexington, she presents an absorbing, exciting account that will transport you back to the raucous beginning of American horse racing and introduce you to the stallion at its heart"--